PELATIHAN LIVE VIDEO STREAMING MENGGUNAKAN APLIKASI TIKTOK DI POSYANDU ASOKA II JATIRANGGON BEKASI - Kustian, Nunu; Siti Julaeha; Wulan Anggraeni (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Digital platform are growing by providing various infrastructure, one of which is live video streaming on the TikTok application which is widely downloaded in Indonesia, which ranks second in 2022. The live can be utilized with positive activities and cause public reaction at the activities of Posyandu Asoka II Jatiranggon Bekasi. But in reality, Posyandu cadres only use smartphones to chat on certain applications such as Whatsapp, take photos, do recording, and store important files. Some cadres already have a TikTok account but only view, and comment on videos passing by on the homepage of their account, sometimes uploading videos as a variation of life if free time. Based on the observations that have been made, the abdimas team conducts training to better utilize the TikTok application for activities carried out directly so that it can attract viewers or other TikTok users to interact in the comment column, even viewers can give awards (tap-tap screen), gifts in the form of coins on each image and can join in the live broadcast that is done. The results of the training have received appreciation, and the addition of the latest technology knowledge so that it motivates cadres to be able to live regularly.